Exterior of the Mandapa (pillared hall) of the Mahanaleshwar Temple - Temples of India Project Team (Jio Institute, 2024)
Seen here are the details of the base plinth and kakshasana (seat backs) vedika (railing) of the lateral transepts of the Mahanaleshwar Temple mandapa (pillared hall). The corner plinth has a devakoshtha (niche) with a sculpture that is likely of Ganga. It is identifiable with the depiction of the makara (crocodile-like creature), which is at the bottom left of the deity. The identification of sculpture of Ganga is identified based on the depiction of the makara (crocodile-like creature), which is at the bottom left of the deity. The introduction of this sculpture to the vedika (railing), which otherwise has the icons of dikapalas (gods of cardinal directions), is noteworthy.